2018
DOI: 10.3324/haematol.2018.188664
|View full text |Cite
|
Sign up to set email alerts
|

ActivinA: a new leukemia-promoting factor conferring migratory advantage to B-cell precursor-acute lymphoblastic leukemic cells

Abstract: B-cell precursor-acute lymphoblastic leukemia modulates the bone marrow (BM) niche to become leukemia-supporting and chemo-protective by reprogramming the stromal microenvironment. New therapies targeting the interplay between leukemia and stroma can help improve disease outcome. We identified ActivinA, a TGF-β family member with a well-described role in promoting several solid malignancies, as a factor favoring leukemia that could represent a new potential target for therapy. ActivinA resulted over-expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…In liver metastasis, for instance, Activin A produced by the target organ was reported to promote metastasis formation [56]. In the bone marrow niche, activin A production by stromal cells was induced by B-cell precursor-acute lymphoblastic leukemic cells and provided a migratory advantage for leukemic cells over healthy hematopoiesis [57]. Overall, the great majority of studies conclude that activin A has a promigratory and prometastatic function and its inhibition could be used to prevent or reduce metastatic spreading.…”
Section: Activin a In Migration Invasion And Metastasismentioning
confidence: 99%
“…In liver metastasis, for instance, Activin A produced by the target organ was reported to promote metastasis formation [56]. In the bone marrow niche, activin A production by stromal cells was induced by B-cell precursor-acute lymphoblastic leukemic cells and provided a migratory advantage for leukemic cells over healthy hematopoiesis [57]. Overall, the great majority of studies conclude that activin A has a promigratory and prometastatic function and its inhibition could be used to prevent or reduce metastatic spreading.…”
Section: Activin a In Migration Invasion And Metastasismentioning
confidence: 99%
“…ActivinA, in turn, caused enhanced cell motility, migration toward CXCL12, and the invasion of B-cell precursor (BCP)-ALL cells as determined by time-lapse microscopy. Furthermore, this in vitro finding was verified by the enhanced in vivo engraftment of BCP-ALL cells to BM and extramedullary sites (peripheral blood, spleen, liver, meninges, and brain) in a xenograft mouse model [ 16 ]. Recent developments in imaging technologies have provided powerful new tools to visualize, image, track, and analyze HSCs and their interactions with the BM niche by labeling with fluorescent dyes such as Qdot 655 [ 17 ].…”
Section: Introductionmentioning
confidence: 90%
“…The interaction between mesenchymal stromal cells (MSCs) and leukemia cells has been of much interest. Leukemia cells have been described to remodulate the BM microenvironment via stimulating MSCs to release more ActivinA, a pleiotropic cytokine that belongs to the TGF-β superfamily [ 16 ]. ActivinA, in turn, caused enhanced cell motility, migration toward CXCL12, and the invasion of B-cell precursor (BCP)-ALL cells as determined by time-lapse microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, CXCL12, secreted by BM-MSCs, plays an essential role in maintaining the quiescent BM hematopoietic stem cell pool. Independent studies on BM plasma samples of pediatric B-ALL patients at disease diagnosis have demonstrated a dramatic decrease in this chemokine [ 61 , 62 , 63 ]. Alongside, ALL-MSCs have been shown to secrete significantly lower CXCL12 compared to MSCs isolated from healthy donors (HD-MSCs) [ 64 ].…”
Section: The Bm Niche In Overt B-all: a Corrupted Microenvironment Reprogrammed To Sustain Leukemic Cellsmentioning
confidence: 99%